Gold as an Investment Option in India : Myth and Reality - Panda, Rajesh; Sethi, Madhvi (Indian Journal of Finance, 2016)
The trend of gold demand in India has been growing continuously. Global physical demand of gold increased by 34% for the time period from 2004-2013 ; whereas, physical demand of gold in India increased by more than 40% for the same period. Though India did not count for even 1% of gold production, more than 21% of the global gold consumption was attributed to India in 2013, which was mainly supplied through imports. During the same period, in addition to jewellery, demand for bars and coins also increased substantially, indicating probably that gold is being chosen as a secure investment alternative by Indians. But is gold a good investment option? Is it more reliable than other financial investments? India’s fascination for the yellow metal - is a reality or is it a myth? Gold as an investment option for an Indian investor was analyzed in this paper. Four popular Indian beliefs about gold were examined - (a) gold as an inflation hedge, (b) gold investment as an attractive alternative to fixed income investment, (c) gold investment as a less riskier investment than stock investment, and (d) rupee-dollar exchange rates and its bearing on the returns on gold investment. With a simple statistical analysis of data spanning from a period from 1971-72 to 2012-13, we found evidence for rejection/acceptance of the four beliefs.